2011
DOI: 10.1007/s00436-011-2362-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of helminths in horses in the state of Brandenburg, Germany

Abstract: The objective of the study was to estimate the prevalence of helminths in the horse population of the state of Brandenburg, Germany. One hundred and twenty-six horse farms in the state were selected by randomised stratified sampling. In total, 1,407 horses across all farms were examined coproscopically. The experimental unit was the horse farm: a farm was considered infected when at least one horse on the farm investigated was positive for helminth eggs. Animal details such as age, breed and sex were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
49
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 40 publications
16
49
2
5
Order By: Relevance
“…In the current study, no difference in seroprevalence was found between working horses of different ages, whereas adult horses for slaughter had a higher amount of antibodies. This is similar to the results of Hinney et al (2011), who sampled horses on horse farms in Germany, and reported that younger animals had a higher prevalence of ascarids, which decreased with increasing age, this supports our finding that animals had no difference between the ages and seroprevalence this only of working horses, although it is contrary to what we find in slaughter horses because adult horses presented higher seroprevalence. In our study, there was no difference between breeds of work horses, which is in contrast to that reported in the study by Hinney et al (2011), who reported that heavy horse breeds had a higher risk (OR = 3.63, p = 0.001) of being parasitized, the wild horses presented a OR = 4.94 and p = 0.005, the thoroughbreds while OR was "1" and warmblooded horses or Arabian horses presented OR = 1.07 and p = 0.756, showing that there was a difference between breeds.…”
Section: Discussioncontrasting
confidence: 57%
“…In the current study, no difference in seroprevalence was found between working horses of different ages, whereas adult horses for slaughter had a higher amount of antibodies. This is similar to the results of Hinney et al (2011), who sampled horses on horse farms in Germany, and reported that younger animals had a higher prevalence of ascarids, which decreased with increasing age, this supports our finding that animals had no difference between the ages and seroprevalence this only of working horses, although it is contrary to what we find in slaughter horses because adult horses presented higher seroprevalence. In our study, there was no difference between breeds of work horses, which is in contrast to that reported in the study by Hinney et al (2011), who reported that heavy horse breeds had a higher risk (OR = 3.63, p = 0.001) of being parasitized, the wild horses presented a OR = 4.94 and p = 0.005, the thoroughbreds while OR was "1" and warmblooded horses or Arabian horses presented OR = 1.07 and p = 0.756, showing that there was a difference between breeds.…”
Section: Discussioncontrasting
confidence: 57%
“…From those who returned the questionnaire (second phase population), we took a random sample of 126 farms (third phase population). These farms were then visited to select horses for faecal examination (for details, see Hinney et al 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Cyathostominae currently comprise 13 genera and 52 species (Lichtenfels et al, 1998). In the majority of the European countries studied (Ukraine, Poland, Great Britain, Germany and Italy), the three most prevalent species were Cylicocyclus nassatus, Cylicostephanus longibursatus and Cyathostomum catinatum (Gawor, 1995;Hinney et al, 2011;Kuzmina et al, 2005;2007;Ogbourne, 1976). Only Lichtenfels et al (2001) found Cylicocyclus ashworthi to be the most abundant species in Scotland.…”
Section: Resultsmentioning
confidence: 99%
“…Nematodes of the subfamily Cyathostominae, known also as cyathostomes or cyathostomins, are common in Europe, and a large number of species have been observed (Collobert-Laugier et al, 2002;Hinney et al, 2011;Kuzmina et al, 2005;Kuzmina et al, 2007). These parasites are of enormous interest because of their major diversity, the high infection intensity and serious pathology associated with these infections.…”
Section: Introductionmentioning
confidence: 99%